2018
DOI: 10.1001/jamaneurol.2018.1212
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Galcanezumab for the Prevention of Episodic Migraine

Abstract: IMPORTANCE Migraine is a disabling neurological disease characterized by severe headache attacks. Treatment options reduce migraine frequency for many patients, but adverse effects lead to discontinuation in many patients. OBJECTIVE To demonstrate that galcanezumab is superior to placebo in the prevention of episodic migraine with or without aura. DESIGN, SETTING, AND PARTICIPANTS The EVOLVE-1 (Evaluation of LY2951742 in the Prevention of Episodic Migraine 1) trial was a double-blind, randomized, placebo-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
674
1
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 473 publications
(720 citation statements)
references
References 38 publications
31
674
1
14
Order By: Relevance
“…11 Galcanezumab is a humanized monoclonal antibody that potently and selectively binds to the CGRP ligand 12,13 and is approved for the preventive treatment of migraine in adults. 19,20 There were also no clinically meaningful differences between the 2 galcanezumab doses with respect to safety profiles. [19][20][21] In EVOLVE-1 (NCT02614183) and EVOLVE-2 (NCT02614196), patients with episodic migraine treated with monthly galcanezumab of 120-mg or 240-mg doses had a greater decrease from baseline than did placebo-treated patients in the average number of MHDs per month over the 6 , with no statistically significant differences between the 2 galcanezumab doses in either study.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…11 Galcanezumab is a humanized monoclonal antibody that potently and selectively binds to the CGRP ligand 12,13 and is approved for the preventive treatment of migraine in adults. 19,20 There were also no clinically meaningful differences between the 2 galcanezumab doses with respect to safety profiles. [19][20][21] In EVOLVE-1 (NCT02614183) and EVOLVE-2 (NCT02614196), patients with episodic migraine treated with monthly galcanezumab of 120-mg or 240-mg doses had a greater decrease from baseline than did placebo-treated patients in the average number of MHDs per month over the 6 , with no statistically significant differences between the 2 galcanezumab doses in either study.…”
Section: Introductionmentioning
confidence: 90%
“…10 A recent study evaluated cycling of preventive migraine medications from a claims database and found that for patients with episodic and chronic migraine, more than 75% of patients switched or discontinued their initial preventive treatment within 12 months, leading to increased healthcare resource utilization and cost. [19][20][21] In EVOLVE-1 (NCT02614183) and EVOLVE-2 (NCT02614196), patients with episodic migraine treated with monthly galcanezumab of 120-mg or 240-mg doses had a greater decrease from baseline than did placebo-treated patients in the average number of MHDs per month over the 6 , with no statistically significant differences between the 2 galcanezumab doses in either study. 14,15 The efficacy, safety, and tolerability of galcanezumab for migraine prevention have been established in 2 Phase 2 studies 16-18 and 3 Phase 3 studies.…”
Section: Introductionmentioning
confidence: 99%
“…The full description of patient disposition is provided in previous publications 17, 18. Table 1 presents the baseline demographics and the disease characteristics for the 2 galcanezumab dose groups and the placebo group.…”
Section: Resultsmentioning
confidence: 99%
“…76,77 Patients were randomized to either galcanezumab 240 mg monthly, 120 mg monthly following a loading dose of 240 mg, or placebo. 76,77 Patients were randomized to either galcanezumab 240 mg monthly, 120 mg monthly following a loading dose of 240 mg, or placebo.…”
Section: Cgrp Monoclonal Antibodiesmentioning
confidence: 99%
“…76,77 Patients were randomized to either galcanezumab 240 mg monthly, 120 mg monthly following a loading dose of 240 mg, or placebo. 76 EVOLVE-2 reported MDD reduction of −2.0 days (120 mg) and −1.9 days (240 mg). 76,77 Further studies also found a significant reduction in acute medication use.…”
Section: Cgrp Monoclonal Antibodiesmentioning
confidence: 99%